ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL CERITA PADA MATERI LUAS PERMUKAAN BANGUN RUANG BERDASARKAN NEWMAN’S ERROR ANALYSIS (NEA) DITINJAU DARI KEMAMPUAN SPASIAL - Mulyadi Mulyadi; Riyadi Riyadi; Sri Subanti (Jurnal Pembelajaran Matematika, 2015)
Abstract: Newman’s Error Analysis (NEA) is a method to analyze the error occurring in the students. One of the main factors which causes the weakness of the students comprehension toward polyhedral material is spatial ability. This study aims at describing  error occurred in the students based on NEA viewed from spatial ability. The information of that error occurence can be used as a means of consideration in deciding the appropiate lesson plan. This study was a descriptive qualitative research with case study method. The subjects of research were the semester VIII  graders  of  SMPN  2  Kebonagung  in academic year of 2013/2014, there were 12 students who have hight spatial ability, 11 students who have medium spatial ability and 11 students who have low spatial ability. The sampling technique used was purposive sampling. The data were taken from the result of error diagnostic test which was followed by Certainly of Response Index (CRI) scores, spatial test and interview. The validity of data used triangulation techniques. The data was analyzed by using Miles and Huberman’s model. The result of research showed that based on NEA in the subject of hight spatial ability was 4,65% reading error, 13,95% comprehension error, 27,91% transformation error, 25,58% process skill error and 27,91% encoding  error. Medium spatial ability subjects obtain 2,94% reading error, 2,94% comprehension error, 32,35% transformation error, 29,41% process skill error and 32,35% encoding error. Subjects of low spatial ability obtain 3,03% reading error, 9,09% comprehension error, 30,30% transformation error, 27,27% process skill error and 30,30% encoding error. The errors are mainly made by the subjects because of the concept incomprehensibility, then misconception and the lowest one is the subjects comprehend the concept but they are careless in doing the assignment.Keyword: error, NEA, concept incomprehensibility, misconception, comprehend the concept